Sustainability of pacific white shrimp culture strategies during regional outbreak of white spot syndrome virus - Junior, Ambrosio Paula Bessa; Valenti, Wagner Cotroni [UNESP]; Flickinger, Dallas Lee; Henry-Silva, Gustavo Gonzaga (Boletim do Instituto de Pesca, 2024)
The present study evaluated economic, environmental, and social sustainability of three production strategies of Pacific white shrimp (Litopenaeus vannamei) during a regional outbreak of white spot syndrome virus. The strategies mainly differed by stocking densities (92, 14, 8 larvae·m-2; D92, D14, and D8, respectively), fertilizer inputs, and other general management. Each dimension of sustainability was evaluated using sets of indicators. The D14 and D8 strategies showed greater economic feasibility than D92 because of the reduced operational costs and investments to buy post-larvae and feed. All strategies showed moderate environmental sustainability, but they had weakened economic and social sustainability due to the virus. The D14 (60) and D8 (62) strategies received the highest overall sustainability index. The D92 was the most environmentally favorable management strategy and social trend. In general, shrimp mariculture with a high initial stocking density cannot guarantee the return of the invested capital. The lower density strategies were economically viable due to the high prices paid per kilogram of shrimp due to the higher individual average weight and reduced apparent feed conversion ratio (D14 = 1.44 and D8 = 0.22). However, economic feasibility of these two strategies coincided with low creation of employment opportunities and income, decreased social sustainability, and increased environmental impact.
Estratégias de sustentabilidade no cultivo do camarão-branco-do-pacífico durante um surto regional do vírus da síndrome da mancha branca
Keywords: Indicators of sustainability; Ponds; Shrimp aquaculture